Pengaruh Sustainability Report (SR), Corporate Social Responsibility (CSR) Dan Leverage Terhadap Tax Advoidance - Suliawati, Mega; Septiawati, Rohma; Rachpriliani, Awaliawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Tax avoidance, especially if done through tax planning, is a legitimate way to reduce taxes while still complying with tax rules. This study aims to determine the influence of leverage, sustainability report (SR), and corporate social responsibility (CSR) on tax avoidance. Secondary data is one type of data used in this quantitative research procedure. Samples were taken from nineteen mining companies listed on the Indonesia Stock Exchange (IDX) and produced 94 samples between 2018 and 2022. IBM SPSS 26 software was used as a test tool in this study. Sampling was done using purposive sampling techniques